Improving metapragmatic awareness in EFL classroom: is pragmatic consciousness-raising effective? - Abolfathiasl, Hossein; Abdullah, Ain Nadzimah (Universiti Putra Malaysia Press, 2014)
The purpose of the present study was to examine the effect of using pragmatic consciousness-raising activities on EFL learners’ metapragmatic awareness of the speech act of suggesting. Fifty-two Iranian EFL learners in two intact classes were randomly assigned into an experimental group (n=27) and a control group (n=25). A Metapragmatic Awareness Test (MAT) was administered to both groups before the treatment as a pretest, which showed no significant difference between the two groups’ awareness levels. Then, the experimental group received a pragmatic consciousness-raising treatment for eight weeks. After the treatment, first an immediate posttest and then, after eight weeks, a delayed MAT posttest were administered to the participants in both groups to determine the effect of the treatment. The t-test analysis of the delayed posttest mean scores of the experimental and control groups showed a significant difference, indicating the effectiveness of the treatment on the experimental group’s metapragmatic awareness. Additionally, the results of repeated measures of ANOVA showed that the treatment enhanced the experimental group’s awareness in the immediate posttest as well as the delayed posttest, confirming the durability of the effect of the consciousness-raising treatment on these EFL learners’ metapragmatic awareness. The results showed that pragmatic consciousness-raising activities improved EFL learners’ immediate and delayed metapragmatic awareness significantly, thus they can be taken into consideration more seriously in L2 teaching, teacher training and material development.